1979
DOI: 10.1007/bf01317502
|View full text |Cite
|
Sign up to set email alerts
|

Fetal infection of the baboon(Papio cynocephalus) with lymphocytic choriomeningitis virus

Abstract: Recent observations of LCM-induced fetal damage in humans suggested attempts to develop an animal model for studies on viral congenital malformations. We report herein viral studies on three pregnant baboons (Papio cynocephalus) inoculated subcutaneously with LCM virus strain WE3. The first animal, inoculated in the 9th week of pregnancy, aborted 9 days after a high virus dose. Inoculation of the second baboon during a later stage (23rd week) of pregnancy with a moderate virus dose, resulted in the demonstrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…1,8 Neuropathologic studies of human and animal LCMV infection have demonstrated mononuclear cell infiltrates in meninges, choroid plexus, and ependyma. 1,9,10 These observations may explain the obstructive hydrocephalus observed in both congenital and acquired LCMV infections with central nervous system involvement.…”
Section: Discussionmentioning
confidence: 87%
“…1,8 Neuropathologic studies of human and animal LCMV infection have demonstrated mononuclear cell infiltrates in meninges, choroid plexus, and ependyma. 1,9,10 These observations may explain the obstructive hydrocephalus observed in both congenital and acquired LCMV infections with central nervous system involvement.…”
Section: Discussionmentioning
confidence: 87%
“…Mittlerweile gelang es, diese Beobachtungen in Versuchen an Pavianen zu bestätigen. Durch eine Infektion des Muttertieres mit LCM-Virus ließen sich beim Fetus die gleichen Krankheitserscheinungen wie beim Menschen auslösen (2). Unabhängig von uns wies mittlerweile Sheinbergas in Wilna/UdSSR wiederholt bei Kindern mit den von uns beobachteten angeborenen Schäden LCM-Virusantikörper nach (12).…”
unclassified